2019
DOI: 10.1002/aur.2195
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition as a predictor of functional and social skills in autistic adults without intellectual disability

Abstract: Autistic adults, including those without intellectual disability, commonly experience poor social and functional outcomes. Although reduced social cognitive ability in autism is often theorized as a mechanism of these poor outcomes, there has been surprisingly little empirical work testing this assumption. Here, 103 autistic adults without intellectual disability completed a comprehensive battery that included eight social cognitive tasks psychometrically validated for use with this population (e.g., emotion r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 71 publications
2
30
0
1
Order By: Relevance
“…They reported that female subjects with ASD performed better on those tests than male subjects with ASD did. Other reports have described non-significant results in terms of ToM [ 24 , 27 ]. One explanation is expected to be that the current findings were driven by the few female subjects in the sample.…”
Section: Discussionmentioning
confidence: 95%
“…They reported that female subjects with ASD performed better on those tests than male subjects with ASD did. Other reports have described non-significant results in terms of ToM [ 24 , 27 ]. One explanation is expected to be that the current findings were driven by the few female subjects in the sample.…”
Section: Discussionmentioning
confidence: 95%
“…Interpersonal interactions are a rich source of social information, and it is possible autistic individuals may be placing greater emphasis on some information more than others, or have their rapport limited by the volume of interactional processing going on (Murray et al, 2005). Second, due to well-documented autistic differences in social cognition (e.g., Sasson et al, 2020) autistic people may underestimate their rapport due to negative self-perception of their social skills (Hull et al, 2017) or lower self-perceived social competence (Jamison and Schuttler, 2015). Poor self-perception may also be the consequence of having a history of negative social interactions with individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Nonverbal and verbal communicative behaviors, including facial expressions, eye contact, postural mirroring, and tone play an important role in building rapport in people presumed to be neurotypical (Tickle-Degnen and Rosenthal, 1990); while not exhibiting these behaviors is related to poorer rapport (Richmond and McCroskey, 1995;Grahe and Bernieri, 1999;Hove and Risen, 2009). As difficulties with processing and expressing verbal and non-verbal social cues amongst autistic individuals have been well documented (Bottema-Beutel et al, 2019;Sasson et al, 2020), we might expect this to subsequently impact upon their development of rapport with others.…”
Section: Introductionmentioning
confidence: 99%
“…Social isolation and community-living impairment resulting from these socio-cognitive deficits are common features in individuals with ASD ( 19 21 ), often leading to lower quality of life ( 22 24 ). These SC deficits appear to have an impact on functional and social skills in subjects with ASD also in the presence of a normal Intelligence Quotient (IQ) ( 25 ).…”
Section: Introductionmentioning
confidence: 99%